Utilization of Memrise Application to Improve Arabic Speaking Skill - Rasyidah, Nafiatur; Halimi, Halimi; Ramadhan, Muhammad Fadli; Ibrahim, Faisal Mahmoud Adam (Borneo Journal of Language and Education, 2025)
This study aims to conduct a pilot study on the utilization of Memrise application to improve student’s Arabic speaking skill at MAN 2 Yogyakarta. Through the Single Subject Research (SSR) method, with the Multiple Baseline Design Across Subject model, this study seeks to reveal the functional relationship between the treatment in the form of utilizing the Memrise application and student’s Arabic speaking skill. This study involved 3 subjects with learning difficulties. Data collection in the form of the level of Arabic speaking skill is carried out through the oral test method which is carried out repeatedly starting from the base line phase to the intervention phase. The measurement data were then analyzed through visual analysis within conditions and between conditions. Through the analysis process, it is known that the data trend of the three subject’s Arabic speaking skill has increased after the intervention. The results of this study become an important basis for lesson planning that targets the achievement of certain Arabic speaking skills by utilizing technology-based media. The selection of media supporting Arabic speaking skills should facilitate learners to practice oral communication continuously.